"Great writers" (W. Scott; etc., etc., 1887)
1. Life of Jane Austen/ Goldwin Smith.-- 2. Honore de Balzac/ Frederick Wedmore.-- 3. Robert Browning/ William Sharp.-- 4. John Bunyan/ Edmund Venables.-- 5. Robert Burns/ John S. Blackie.-- 6. Lord Byron/ Roden Noel.-- 7. Thomas Carlyle/ Richard Garnett.-- 8. Miguel de Cervantes/ Henry E. Watts.-- 9. Samuel Taylor Coleridge/ Hall Caine.-- 10. William Congreve/ Edmund Gosse.-- 11. George Crabbe/ T.E. Kebbel.-- 12. Charles Darwin/ G.T. Bettany.-- 13. Charles Dickens/ Frank T. Marzials.-- 14. George Eliot/ Oscar Browning.-- 15. R.W. Emerson/ Richard Garnett.-- 16. Johann Wolfgang Goethe/ James Sime.-- 17. Oliver Goldsmith/ Austin Dobson.-- 18. Nathaniel Hawthorne/ Moncure D. Conway.-- 19. Heinrich Heine/ William Sharp.-- 20. Victor Hugo/ Frank T. Marzials.-- 21. Leigh Hunt/ Cosmo Monkhouse.-- 22. Samuel Johnson/ Lieut.-Col. F. Grant.-- 23. John Keats/ William M. Rossetti.-- 24. Gotthold Ephraim Lessing/ T.W. Rolleston.-- 25. Henry Wadsworth Longfellow/ Eric S. Robertson.-- 26. Maurice Maeterlinck/ Jethro Bithell.-- 27. Frederick Marryat/ David Hannay.-- 28. John Stuart Mill/ W.L. Courtney.-- 29. John Milton/ Richard Garnett.-- 30. Ernest Renan/ Francis Espinasse.-- 31. Friedrich Schiller/ Henry W. Nevinson.-- 32. Arthur Schopenhauer/ W. Wallace.-- 33. Sir Walter Scott/ Charles D. Yonge.-- 34. Percy Bysshe Shelley/ William Sharp.--35. Richard Brinsley Sheridan/ Lloyd C. Sanders.-- 36. Adam Smith/ R.B. Haldane.-- 37. Tobias George Smollett/ David Hannay.-- 38. W.M. Thackeray/ Herman Merivale and Frank T. Marzials.-- 39. Life and Writings of Henry David Thoreau/ Henry S. Salt.